A Probabilistic Model Of Learning Fields Applied to a Foundational Theory of Islamic Economics and Finance - Choudry, M. A. (Universiti Sains Islam Malaysia, 2024)
An epistemological model of learning fields of probabilistic events is formalized. It is used to explain resource allocation that is governed by pervasive complementarities as the sign of unity of knowledge that is induced epistemologically into interacting, integrating and evolutionary variables representing the problem at hand. The end result is formalization of a probabilistic model of learning that has no optimal points. In it variables and their representations simply learn continuously and generate evolutionary general equilibrium points. Such points can be computed by computational general equilibrium under the impact of learning in unity of knowledge. Of all approaches 10 such a study only the doctrine of the paired universe of the Qur'an stands out as unique. In this regard the Qur'an says (36:36), "Glory to God, Who created in pairs all things that the earth produces, as well as their own kind and things of which they have no knowledge."Upon the episteme of unity is constructed the probabilistic model of learning fields. In it we refer to the specific issue of money-real economy linkages as a resource mobilization problem involving an asset valuation approach. Some empirical evidence is placed in respect of the consequences expected from the study of probabilistic models of learning fields applied to economic and financial problems.